The human flea Pulex irritans (Siphonaptera: Pulicidae) in northwestern Argentina, with an investigation of Bartonella and Rickettsia spp. = La pulga humana Pulex irritans (Siphonaptera: Pulicidae) en el noroeste argentino, una investigación de Bartonella y Rickettsia spp. - Lareschi, Marcela (2018)
Pulex irritans is the only cosmopolitan flea species and the most studied one within the genus Pulex. It has importance in public health since it commonly parasitizes humans causing dermatitis, and it has been also implicated in the transmission of bacterial pathogens. Pulex irritans has been confused with the closely related Pulex simulans species for years. Herein, Pulex specimens collected from a Pampas fox and a Chacoan peccary from northwestern Argentina were identified by comparison with type specimens. In addition, the presence of Bartonella spp. and Rickettsia spp. was investigated using PCR assays. Our results provided characters of diagnostic importance to identify P. irritans, which include the shape of sternite VII in the females, and of the aedeagal sclerite, clasper and crochet in the males. Besides, we report for the first time P. irritans parasitizing a peccary. This finding reinforces the hypothesis of the origin of this flea associated with this mammal, and then colonizing humans and domestic mammals. There was no evidence of Bartonella or Rickettsia DNA in the analyzed fleas. This information even if negative may be considered relevant for P. irritans from Argentina.